A series of confusing measurements in the search for water. Issue 1 (1st December 2019) - Wijns, Chris
Summary: A mine development in the high Andes of north-western Argentina requires a supply of fresh water for various uses, the largest being mineral processing. Complementary survey techniques in a gravel basin have provided vastly different and sometimes contradictory results. Mapping of the basin geometry proceeded via downhole resistivity logging, moving loop ground EM, and galvanic resistivity. The expected layering of low resistivity gravel fill over high resistivity basement rock, which was demonstrated by prior downhole logging, was turned on its head by surface electrical and EM surveys. Furthermore, subsequent borehole resistivity logs, which do not reach bedrock, support the increase of conductivity with depth, while water sampling indicates this is not due to greater salinity. Surface nuclear magnetic resonance was trialled for the direct detection of the upper part of the water table. The majority of these data were contaminated by mysterious noise sources in an area hundreds of kilometres from the nearest atmospheric activity, and fifty kilometres from the closest settlement. False negative readings appear to be common. The most recent drilling, demonstrating much deeper gravel than previously drilled or imagined, may explain an inability to image the bottom, but the reason for the deep conductivity remains a mystery.